An examination of major works for concert band and chamber ensembles: Down a Country Lane by Aaron Copland, Two Pieces from Lieutenant Kije by Sergei Prokofiev, and Suite in B-flat by Richard Strauss - Roth, Emily Renee (Kansas State University, 2015)
The following report is a detailed analysis on the following three pieces: Suite in B-flat by Richard Strauss for woodwind chamber ensemble, Two Pieces from Lieutenant Kije by Sergei Prokofiev for brass and percussion ensemble, and a finally Down a Country Lane by Aaron Copland for concert band. The goal of the analysis is to provide rehearsal information for educational purposes. Aspects of the compositions studied include: background information on the composer and composition, a historical perspective, technical and stylistic considerations, and the musical elements. The researchers perspective on philosophy of music education is also stated as well as the importance of choosing quality literature for pedagogical needs and performance. The goal of this report is to aid future conductors in their performances of the literature and for that reason the seating charts for the ensembles, acoustical justifications, as well as rehearsal plans have been included.
Keywords: Richard Strauss; Sergei Prokofiev; Aaron Copland; Concert band; Conducting; Music Education (0522)